Potential of mesenchymal stem cell therapy. - Dazzi, F; Horwood, N (2007)
PURPOSE OF REVIEW: Mesenchymal stem cells have the capacity to differentiate into several mesenchymal tissues, including the components of the hematopoietic stem cell niche. Mesenchymal stem cells also exhibit a powerful immunosuppressive activity. Here we review the most recent data to identify the properties of therapeutic significance. RECENT FINDINGS: Mesenchymal stem cells are attractive not only in regenerative medicine but also for the treatment of autoimmune diseases and graft-versus-host disease. Initial experience in animal models and the clinical setting have produced very encouraging results whereby mesenchymal stem cells have been shown to accelerate recovery after myocardial infarction, improve growth velocity in children with osteogenesis imperfecta, and ameliorate severe graft-versus-host disease as well as, in mouse models, rheumatoid arthritis and multiple sclerosis. Their use in the clinical setting, however, must be considered with caution because there is evidence that mesenchymal stem cells may also contribute to the maintenance of cancer stem cells. SUMMARY: The interest generated by mesenchymal stem cells has rapidly favored several initiatives to test their therapeutic potentials. There is still much to investigate to characterize their phenotype, understand their mechanisms of action, and optimize their in-vitro expansion for clinical use.